2016
DOI: 10.1590/1519-6984.13514
|View full text |Cite
|
Sign up to set email alerts
|

Habitat architecture influencing microcrustaceans composition: a case study on freshwater Cladocera (Crustacea Branchiopoda)

Abstract: Environmental complexity is considered a key factor for diversity enhancement in aquatic ecosystems. Macrophyte stands are a major contributor for this complexity due to their differential architectures. Nevertheless, the influence of distinct aquatic habitat architectures (with different types of macrophytes or without them) on microcrustaceans' taxa composition, usually found in macrophyte colonized water bodies, is underexplored in limnological studies. The main objective of this study was to analyze this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…For submerged aquatic vegetation (SAV), the increase in zooplankton biomass and functional diversity was also related to the increased availability of habitats and ecological niches provided by submerged macrophyte structures [39]. Increased abundance of organisms in the macrophyte mesocosms with the attached feeding type, benthic habitat preference, as well as the herbivore-detritivore trophic grouping together reflects their feeding strategy consisting of scraping the surfaces of submerged branches of macrophytes for periphyton or accumulated detritus on macrophyte roots [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For submerged aquatic vegetation (SAV), the increase in zooplankton biomass and functional diversity was also related to the increased availability of habitats and ecological niches provided by submerged macrophyte structures [39]. Increased abundance of organisms in the macrophyte mesocosms with the attached feeding type, benthic habitat preference, as well as the herbivore-detritivore trophic grouping together reflects their feeding strategy consisting of scraping the surfaces of submerged branches of macrophytes for periphyton or accumulated detritus on macrophyte roots [3].…”
Section: Discussionmentioning
confidence: 99%
“…In aquatic ecosystems, the presence of macrophytes has important structuring consequences for microcrustacean communities because their physical characteristics alter habitat structure in ways that can influence resource availability and resource quality [1,2]. It has been reported that for cladocerans, the habitat architecture is an important factor influencing composition [3]. For example, macrophytes increase the availability of attachment surfaces for species that require a substrate for locomotion such as benthic cladocerans, or for species able to use submerged structures to settle and filter water from a stationary position.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Habitat complexity in the freshwater ecosystem plays an important role in the growth and distribution of aquatic organisms (Meerhoff et al, 2007;Debastiani-Júnior et al, 2016). Generally, animal abundance and species richness are considerably higher where submerged macrophytes are present (Hemminga and Duarte, 2000).…”
Section: Introductionmentioning
confidence: 99%